BILL NO. 1.057/2007 ON THE CRIMINALIZATION OF INDIGENOUS PEOPLE AND THE VIOLATION OF CONSTITUTIONAL RULES (Isagoge - Journal of Humanities and Social Sciences, 2023)
Indigenous peoples in Brazil once practiced indigenous infanticide and today there are still reports that they continue to practice, thus violating the right to life. This scientific article aims to briefly bring reports of deaths of children by their own relatives and the great debate of to what extent they are true. Still, it aims to discuss the Bill 1.057/2007 that criminalizes indigenous infanticide, in the light of the constitutional principles involved and data on the reasons that gave rise to this practice. Finally, it analyzes the possible forms of state intervention in cases of infanticide within the villages. This research included a legal and documentary methodology to analyze the aforementioned bill, the constitutional principles involved in the theme and the collision of norms. In short, the Bill 1.057/2007 analyzed proves to be unnecessary and lacking in legal relevance, insofar as it is not in line with constitutional dictates. In addition, the research also estimated that there are no reliable data on the practice of indigenous infanticide today, due to the great obscurity that persists under the subject.
Keywords: Native peoples. Infanticide. Cultural diversity.